Measuring physical activity-related environmental factors: reliability and predictive validity of the European environmental questionnaire ALPHA. - Spittaels, H; Verloigne, M; Gidlow, C; Gloanec, J; Titze, S; Foster, C; Oppert, J; Rutter, H; Oja, P; Sjöström, M; De Bourdeaudhuij, I (2010)
BACKGROUND: A questionnaire to assess physical activity related environmental factors in the European population (a 49-item and an 11-item version) was created as part of the framework of the EU-funded project "Instruments for Assessing Levels of PHysical Activity and fitness (ALPHA)". This paper reports on the development and assessment of the questionnaire's test-retest stability, predictive validity, and applicability to European adults. METHODS: The first pilot test was conducted in Belgium, France and the UK. In total 190 adults completed both forms of the ALPHA questionnaire twice with a one-week interval. Physical activity was concurrently measured (i) by administration of the long version of the International Physical Activity Questionnaire (IPAQ) by interview and (ii) by accelerometry (Actigraph device). After adaptations, the second field test took place in Belgium, the UK and Austria; 166 adults completed the adapted questionnaire at two time points, with minimum one-week interval. In both field studies intraclass correlation coefficients (ICC) and proportion of agreement were computed to assess the stability of the two test scores. Predictive validity was examined in the first field test by correlating the results of the questionnaires with physical activity data from accelerometry and long IPAQ-last 7 days. RESULTS: The reliability scores of the ALPHA questionnaire were moderate-to good in the first field testing (ICC range 0.66 - 0.86) and good in the second field testing (ICC range 0.71 - 0.87). The proportion of agreement for the ALPHA short increased significantly from the first (range 50 - 83%) to the second field testing (range 85 - 95%). Environmental scales from both versions of the ALPHA questionnaire were significantly associated with self-reported minutes of transport-related walking, and objectively measured low intensity physical activity levels, particularly in women. Both versions were easily administered with an average completion time of six minutes for the 49-item version and less than two minutes for the short version. CONCLUSION: The ALPHA questionnaire is an instrument to measure environmental perceptions in relation to physical activity. It appears to have good reliability and predictive validity. The questionnaire is now available to other researchers to investigate its usefulness and applicability across Europe.